Yes/No Questions and Structure-Dependency in Syrian Arab L2 Users of English (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Testing the structure-dependency principle in second language acquisition research means showing if the structure-dependency in question is part of second language learners’ interlanguage or not regardless of whether learners L1 has a syntactic movement or not.This research adopts the descriptive approach and its empirical work on the grammatical phenomenon in the analysis using SPSS. In this research, a group of second language learners (SLLs) of English have been asked to judge if 6 sentences are grammatical or not, using the Oxford Placement Test 2 (Allan, 2004) grammaticality judgement test. The sentences are yes/no questions, some of which violate the structure-dependency principle and the others are grammatical. The study has been conducted on SLLs of English in Tishreen University, Syria.This research aims to investigate whether Syrian Arab learners of English can detect the structure-dependency principle in English yes/no questions; a question structure in which the structure-dependency does not operate in Syrian Arabic.The results of the study show that the two groups perform differently. The pre-intermediate learners achieve a higher frequency of appropriate answers compared to beginner’s appropriate answers. Although the pre-intermediate group perform better, the results revealed in the data will be used to investigate the role of Chomsky’s concept of Universal Grammar (UG) in Second Language Acquisition (SLA).